Designed an Inactive Archives Management Information System Using Visual Basic 2010 at The Department of Community Empowerment and Village West Java Province - Abdurrahman Nur Alfath; Intan Taningngsih; Edi Suharto (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
In the field of archive depots, the West Java Province Village and Community Empowerment Service offers inactive archive management as one of its services. The West Java Province Village and Community Empowerment Service is responsible for keeping, organizing, and safeguarding archives that have been in the processing unit for more than two years. The goal of this research is to help archivists manage inactive archives more effectively and efficiently. Material gathering tactics included interviews and the addition of inactive archive data based on data collected in each field. Software is designed using the waterfall process. According to the findings, there are a number of issues that impede the archive management system that still employs the manual method. As a result, in this study, an inactive records management information system was designed using the Unified Modeling Language (UML) and implemented using the Visual Basic programming language with the.NET framework 4.0 and Ms. Access as the database. An approach for testing applications is called black box testing. The goal of this application is to make archive administration more effective and efficient.